Analysis of TENORM Using Phytoremediation Technics in the Environment Gas Industry - R. Safitri; . Irhamni; . Samsinah (Syiah Kuala University, 2012)
TENORM (technologically enhanced naturally occurring radioactive material) is the natural radioactivity due to human activity or process technology has increased the potential radiation exposure, compared to the initial state. TENORM focuses on the results of the waste industry. Testing the existence of TENORM in the industry has been made on the LNG plant in Aceh. The study aims at observing chances TENORM contamination at the factory working environment. The study was done by using Phytoremediation uses kale plants growing around an industrial environment. The analysis is done by calculating transfer factors from waste radioactive material into kale plants by comparing the results on the industry instead. The results showed that the value of measurements on samples of chopped watercress growing in the industry is higher than the count values in the samples grown in the industry instead. Increased count values above 100% when measured in the roots, stems and leaves. It is informed that the radioactive contamination of the environment from the possible gas industry TENORM contaminated presence in the neighbourhood